Mite Pests of Southern Highbush Blueberry in Florida - Oscar Liburd; Lorena Lopez; Doug Phillips (EDIS)
Several mite species attack southern highbush blueberries (SHB), including the southern red mite (Oligonychus ilicis McGregor (Acari: Tetranychidae)), the false spider mite or flat mite (Brevipalpus yothersi Baker) and the blueberry bud mite (Acalitus vaccinii Keifer). The southern red mite is the key mite pest attacking blueberry plants in the southeastern US (Lopez and Liburd 2020). The false spider mite is a secondary leaf feeding mite pest that was reported attacking southern highbush blueberry in 2016 (Akyazi et al. 2017). This publication discusses southern red mites and flat mites on SHB in Florida, including life cycle, damage, and management practices.